1980
DOI: 10.1159/000179110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of a Pineal Extract on Adrenal Cortex Lack of Competition with ACTH

Abstract: The purpose of the present investigation was to study the mode of action of a crude aqueous pineal extract (CAPE) on corticosterone (B) production from ACTH-mediated isolated adrenal cortex cells. Corticosterone production from a heterogenous adrenal cortex cell population, isolated from 8 male Sprague-Dawley rats, was measured fluorimetrically. CAPE (25 µl) was tested in this system using ACTH (0–5,000 pg/ml) and dibutyryl-c-AMP (0–100 nA//ml) as stimuli for a period of 1 h. In a separate experiment, CAPE (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Probably, this is closely related to the variations that were found in the activity of the pineal gland of this rodent throughout the year (6). Its action on glomerulosa (25), fasciculata (26) and reticularis zones has been described by other authors. In addition, the results of the reproductive study matched those obtained for the inhibitory action of the pineal on both the pituitary-gonadal and the pituitary-adrenal systems.…”
Section: Discussionsupporting
confidence: 65%
“…Probably, this is closely related to the variations that were found in the activity of the pineal gland of this rodent throughout the year (6). Its action on glomerulosa (25), fasciculata (26) and reticularis zones has been described by other authors. In addition, the results of the reproductive study matched those obtained for the inhibitory action of the pineal on both the pituitary-gonadal and the pituitary-adrenal systems.…”
Section: Discussionsupporting
confidence: 65%
“…Pinealectomy promoted an impressive 2-fold increase in plasma corticosterone levels at all times investigated. Classical studies have shown that melatonin and pinealectomy have a modulatory effect on rat adrenal glands [11,24,25]. In addition, a recent study demonstrated the presence of melatonin receptors in primate adrenals, which inhibited ACTH-stimulated cortisol production [14].…”
Section: Discussionmentioning
confidence: 99%
“…To what extent (if at all) phenomena such as induction, repression, transcription, and translation of gene expression are involved can then be studied at critical times in the feed-sideward. In any event, if the feed-sideward switches the biogenesis of adrenocortical hormones from the path leading to aldosterone or cortisol to that leading to dehydroepiandrosterone, it could account for the fact that both stimulation and inhibition have been reported for pineal effects upon aldosterone production (Farrell, 1959;Fabre et al, 1965) as well as for corticosterone responses (Porter and Heiman, 1977;Heiman and Porter, 1980;Porter, personal communication). Yet more important is the possibility that one may switch competing risks and perhaps one day manipulate such risks to optimize them.…”
mentioning
confidence: 99%